Competencies, roles and effective academic leadership in world class university - Shahmandi, Elham; Silong, Abu Daud; Ismail, Ismi Arif; Abu Samah, Bahaman; Othman, Jamilah (Sciedu Press, 2011)
How an academic leader can become more effective? This research question is examined in the context of middle level leadership in research universities that includes the Deans and Head of Departments. It is based on a review of literature that focuses on the investigation of effective academic leadership. In the present situation of globalization, academic excellence is often related to being World Class University. Leadership effectiveness is more related to situational leadership style in research universities and in a global context. Hence situational leadership models such as Hersey and Blanchard and Yetton-Vroom are analyzed. It is suggested that effective academic leaders use the four styles proposed by Hersey and Blanchard that includes “telling, selling, participating and delegating”. These styles should be used in relation to ability and willingness of followers to perform the assigned tasks. The review also indicated that to be effective, academic leaders require certain competencies and perform the necessary roles in order to lead. Effective academic leaders need the skills and abilities to lead research universities towards excellence. Roles of academic leaders are examined in relation to Mintzberg leadership roles. The ten roles identified by Mintzberg are categorized into three major roles of interpersonal contact, information processing and decision making. To summarize, effective academic leaders utilized various leadership styles according to certain situations, possessed the required competencies and assumed certain roles when appointed as Deans and Head of Departments in research universities. As such it is important that a systematic leadership development programs should be developed to ensure academic leadership effectiveness.